Un second souffle. La danse des búzios au prisme de sa « réaffirmation » culturelle par les Pankararu, Pernambouc, Brésil - Cyril Menta (Journal de la Société des Américanistes)
This article proposes to reflect on the contemporary circulation of indigenous aerophones—known as búzios—and the cultural and political practices associated with them. Based on the case of the dance of the búzios of the Pankararu Indians of the State of Pernambuco, in Brazil, it particularly explores two interwoven dimensions of cultural recovery: one is collective and involves the adoption of a practice, its transformation then its exhibition; the other is individual, through the political rise of a nationally recognized leader.